Australian and New Zealand consensus statement on the management of lymphoma, chronic lymphocytic leukaemia and myeloma during the COVID‐19 pandemic. Issue 6 (15th May 2020) - Di Ciaccio, Pietro; McCaughan, Georgia; Trotman, Judith; Ho, Phoebe Joy; Cheah, Chan Y.; Gangatharan, Shane; Wight, Joel; Ku, Matthew; Quach, Hang; Gasiorowski, Robin; Polizzotto, Mark N.; Prince, Henry Miles; et al.
Abstract: The COVID‐19 pandemic poses a unique challenge to the care of patients with haematological malignancies. Viral pneumonia is known to cause disproportionately severe disease in patients with cancer, and patients with lymphoma, myeloma and chronic lymphocytic leukaemia are likely to be at particular risk of severe disease related to COVID‐19. This statement has been developed by consensus among authors from Australia and New Zealand. We aim to provide supportive guidance to clinicians making individual patient decisions during the COVID‐19 pandemic, in particular during periods that access to healthcare resources may be limited. General recommendations include those to minimise patient exposure to COVID‐19, including the use of telehealth, avoidance of non‐essential visits and minimisation of time spent by patients in infusion suites and other clinical areas. This statement also provides recommendations where appropriate in assessing indications for therapy, reducing therapy‐associated immunosuppression and reducing healthcare utilisation in patients with specific haematological malignancies during the COVID‐19 pandemic. Specific decisions regarding therapy of haematological malignancies will need to be individualised, based on disease risk, risks of immunosuppression, rates of community transmission of COVID‐19 and available local healthcare resources.